Non-Cash Transaction Policy: The Steps for Cashless Management in Central Java Province - Setiawan, Zeffri; Rosidi; Purwanti, Lilik (Accounting Department,, 2022)
Purpose - This study aims to understand the implementation steps of the non-cash transaction policy in the Central Java Provincial Government, with Edward III's (1980)